A teoria do professor reflexivo no processo de formação continuada de professores : uma análise crítica - Barbosa, Silvia Helena Pienta Borges (Universidade Federal de São Carlos, 2016)
The purpose of this research consists in understanding how the reflective teacher theory has guided or/and been basis to continuing education practices in a Regional Education Centre of the São Paulo state. This is a qualitative field research with critical-dialectical approach. The total number of participants in the research was twelve teachers' trainers, including the three pedagogical coordinating teachers of mathematics and the three of Portuguese and at least one elementary school teacher coordinator of each urban state school in the city. The study used as instruments to collect data the semi-structured interview, observation, documentary research, and literature review. The information was analysed using content analysis and data triangulation. The results indicated that the theory of reflective teacher is relevant in legal and guiding documents. However, these documents show just the concepts and elements of this theory that are relevant to the government's interests. Furthermore, the reflective teacher theory in the practice of continuing education is different from both the theory by itself and the theory observed in the legal and guiding documents. In the continuing education practice, the focus in practice happens, but the reflection about the practice does not. Teachers' trainers assume the possibility of reflection by the teachers, using a technical rationality that has not been overcome yet and permeates the actions of continuing education. Moreover, technical rationality encounters the needs of government agencies since it focuses on techniques and tools that lead students to answer the external evaluations satisfactorily. It is concluded that when theories are framed by market reasons, they suffer considerable losses and are used in disconnected and fragmented manners. The theory of reflective teacher, which in its formulation it is not a critical theory and emancipatory, becomes even more distorted and loses its characteristic of reflexivity practice under governmental interests, resulting in an even more uncritical education that does not promote autonomy and empowerment. Thus, it is considered that the critical rationality model would be a possibility for teachers' continuing education because of the relationship between theory and practice, historical contextualization, promotion of emancipation, and critical view.
Keywords: Formação continuada; Professor reflexivo; Formadores de professores; Educação básica; Continuing education; Reflective teacher; Teachers' trainers; Basic education; CIENCIAS HUMANAS::EDUCACAO